Influence Vessel Survey of Shipworthiness (Case Study of PT Makara Jaya Marine Client) - Lisa Annur Arum Janah; Larsen Barasa; Sari Kusumaningrum; Marihot Simanjuntak (Greenation International Journal of Tourism and Management, 2023)
In the offshore oil and gas industry in Indonesia is experiencing development , see the potential for very high demand for offshore installations, such as oil platforms, drilling rigs, etc. As a result, many shipping companies operate offshore vessels, in the activities of mining companies, and operating offshore oil drilling installations, a safety and security system is needed because this is an important factor that must be considered and becomes the basis for decision making in making decisions. determine seaworthiness in shipping, both in terms of facilities in the form of ships and infrastructure such as navigation systems and human resources involved in it, to reduce and minimize an accident on a ship. The purpose of this study is to find out how much influence the ship survey has on the ship's feasibility in the case of a client at PT Makara Jaya Marine. The approach method used is quantitative data , while data collection uses observation techniques, literature studies and questionnaires (questionnaires) so that the causes of problems can be found using quantitative data analysis techniques . The results showed that the effect of the ship survey on shipworthiness in the client case study at PT Makara Jaya Marine based on hypothesis testing with the t test, it was found that t count = 11.169 and after consulting with t table at a significant level of 5% and n = 28 shows t table = 2,048. Because t count is in the rejection area of Ho (11,169 > 2,048) then Ho is rejected and Ha is accepted. The results show that there is a low loading factor weight on the ship survey variable and the shipworthiness variable to overcome it by trying to improve the implementation of the shipworthiness survey in client company periodically to ensure the condition of the ship for safety.